Effect of seasonal drought on the agronomic performance of four banana genotypes (Musa spp.) in the East African highlands - Uwimana, Brigitte; Zorrilla-Fontanesi, Yasmín; Wesemael, Jelle van; Mduma, Hassan; Brown, Allan; Carpentier, Sebastien C.; Swennen, Rony L. (MDPI, 2021)
Banana (Musa spp.), a perennial (sub-)tropical crop, suffers from seasonal droughts, which are typical of rain-fed agriculture. This study aimed at understanding the effect of seasonal drought on early growth, flowering and yield traits in bananas grown in the East African highlands. A field experiment was set up in North Tanzania using four genotypes from different geographical origins and two different ploidy levels. The treatments considered were exclusively rain-fed versus rain supplemented with irrigation. Growth in plant girth and leaf area were promising traits to detect the early effect of water deficit. Seasonal drought slowed down vegetative growth, thus significantly decreasing plant girth, plant height and the number of suckers produced when compared to irrigated plants. It also delayed flowering time and bunch maturity and had a negative effect on yield traits. However, the results depended on the genotype and crop cycle and their interaction with the treatments. “Nakitengwa”, an East African highland banana (EAHB; AAA genome group), which is adapted to the region, showed sensitivity to drought in terms of reduced bunch weight and expected yield, while “Cachaco” (ABB genome group) showed less sensitivity to drought but had a poorer yield than “Nakitengwa”. Our study confirms that seasonal drought has a negative impact on banana production in East Africa, where EAHBs are the most predominant type of bananas grown in the region. We also show that a drought-tolerant cultivar not adapted to the East African highlands had a low performance in terms of yield. We recommend a large-scale screening of diploid bananas to identify drought-tolerant genotypes to be used in the improvement of locally adapted and accepted varieties.